ANALISIS MOTIVASI BELAJAR INTRINSIK PADA PEMBELAJARAN MATEMATIKA KELAS XI SMA NEGERI 1 KEDUNGREJA - Indrayadi, Alviansyah Putra; Rachmanto, Dwi; Lukito, Nandita Ratih Dewi; Rokhisa, Zulfa Nur; Putranto, Sumbaji (Jurnal Pendidikan Matematika (JUPITEK), 2021)
This study aims to analyze the intrinsic learning motivation in mathematics learning in SMA Negeri 1 Kedungreja students. The subjects in this study were a mathematics teacher and 20 students of class XIMIPA 4 SMA Negeri 1 Kedungreja. Qualitative descriptive is the method used in this study. Data collection was carried out by means of questionnaires and interviews. The results showed that there were 15 students with high intrinsic motivation category and 5 students with medium category. Analysis of the average score per indicator for the two categories of intrinsic learning motivation shows that all indicators are in the high category, both high and moderate motivation. However, the highest difference in average scores among the other three indicators is the good habits indicator with a difference of 0.81. This calculation is also confirmed through interviews that students with high intrinsic motivation to learn will study the previous material if tomorrow is the mathematics lesson schedule while students with the intrinsic learning motivation category are stating that if tomorrow is the mathematics lesson schedule they will only look at the previous material